A Statistical Approach for Optimization of Simultaneous Production of β-Glucosidase and Endoglucanase by Rhizopus oryzae from Solid-State Fermentation of Water Hyacinth Using Central Composite Design. (30th May 2011) - Karmakar, Moumita; Ray, Rina Rani
Abstract : The production cost ofβ -glucosidase and endoglucanase could be reduced by using water hyacinth, an aquatic weed, as the sole carbon source and using cost-efficient fermentation strategies like solid-state fermentation (SSF).In the present study, the effect of different production conditions on the yield ofβ -glucosidase and endoglucanase by Rhizopus oryzae MTCC 9642 from water hyacinth was investigated systematically using response surface methodology. A Central composite experimental design was applied to optimize the impact of three variables, namely, substrate concentration, pH, and temperature, on enzyme production. The optimal level of each parameter for maximum enzyme production by the fungus was determined. Highest activity of endoglucanase of 495 U/mL was achieved at a substrate concentration of 1.23%, pH 7.29, and temperature 29.93 ° C whereas maximum β -glucosidase activity of 137.32 U/ml was achieved at a substrate concentration of 1.25%, pH 6.66, and temperature 32.09 ° C.There was a direct correlation between the levels of enzymatic activities and the substrate concentration of water hyacinth as carbon source.